Estabilidade do zooplâncton em face de eventos climáticos em uma planície de inundação Neotropical, Brasil. - Silva, Andressa Crystine Souza da (2024)
In this study, we investigated the stability, resistance, and resilience of zooplankton, estimated through species richness and organism abundance, and how they were influenced by El Niño and La Niña climatic events over 22 years in a Neotropical floodplain. It is expected (i) lower stability during climatic events compared to periods without events, (ii) higher resistance during the La Niña period, and (iii) higher resilience during the El Niño period. The results showed that climatic events affect community stability, particularly during La Niña events, as resistance and resilience were altered, with species richness being especially affected. During the La Niña period, environments undergo changes in size and limnological conditions. Biotic interactions also intensify due to these environmental changes. Nevertheless, the El Niño event also impacts the community, reducing its stability and increasing resilience when organism abundance is considered. Long-term studies are important for describing patterns in the structuring of zooplankton communities in response to hydrological changes caused by climatic events, particularly in anthropogenically impacted floodplain environments.